ANALYSIS OF TNF-α GENE EXPRESSION WITH LIPOPOLYSACCCHARIDE (LPS) AND POLYINOSINIC; POLYCYTIDYLIC ACID (POLY I.C) STIMULATION IN HEAD KIDNEY AND SPLEEN OF CIRRHINUS MRIGALA - 1Mahmood Ul Hassan; 2M. S. Mughal; 3M. I. Sohail; 1M. M. Javed (Journal of Animal and Plant Sciences, 2016)
Tumor necrosis factor alpha (TNF-α) an imperative cytokine is secreted from various immune cells, involved in regulation of inflammation process, leukocytes functioning and secretion of other cytokines. TNF–α has been identified and studied in many bony fishes. In Pakistan, Cirrhinusmrigalais an important farm fish. Being a novel organism, it was selected for the present studies. After acclimation, fish were divided into five groups i.e. control receiving no stimulation, experimental B,C,D and E receiving LPS and Poly I.C, 2 mg and 20 mg/kg body weight respectively through intra-peritoneal injection. These were dissected after 4, 8 and 12 h of injection. Spleen and head kidney were removed and processed for RNA isolation, quantified and used for cDNA synthesis. PCR was performed with TNF-α primers taking cDNA as template. Amplified products were run on 1.2% agarose gel and intensity was calculated by Quality One v.4.5.9 software (BIO-RAD). TNF-α expression was observed significantly up-regulated with 20 mg dose after 4 h of stimulation with LPS but with Poly I.C it was observed after 12 h. Spleen showed elevated expression than head kidney. So the expression level of TNF-α is not only dependent on time and dose of the stimulants but different organs also.
Keywords: TNF-α; Cirrhinusmrigala; head kidney; spleen; LPS; Intra-peritoneal injection